Mengapa Anggota Keluarga Tidak Mengeluarkan Opini? Menyoal Teori Spiral Keheningan di Grup Whatsapp Keluarga - Jeconiah, Calvin; Morissan, Morissan (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study investigates the phenomenon of silence among family members in WhatsApp groups using the Spiral of Silence Theory as its analytical framework. It focuses on how family members often refrain from expressing their opinions in group chats, especially on sensitive topics such as politics. The research aims to identify the underlying factors that lead to this silence and to understand the communication dynamics in digital family interactions. Using a qualitative approach with in-depth interviews and grounded theory analysis, the study finds that collectivist cultural values, family hierarchy, social expectations, and fear of being perceived as disrespectful are key contributors to the spiral of silence. These findings suggest that digital communication platforms do not always encourage open dialogue, even within intimate social units like families.